HISTORIC MOSQUES AND MADRASAS IN KASHKADARYA OASIS - Uzoqov Begali; Jovliev Sardorbek; Alimov Jasur; Dilmurodov Bekzod (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In the process of globalization, complication and acceleration of social processes taking place in our country, the problem of repairing existing historical monuments and mosques in our country and preserving them in their original state arose. For this reason, large-scale restoration and renovation measures were carried out in the years of independence, even in historical mosques located on the territory of the Kashkadarya region.